Pressure field characteristics of petroliferous sags in Bohai Bay Basin: Implication for hydrocarbon enrichment - Youlu Jiang; Xin Wang; Qianqian Yu; Yongshi Wang; Hua Liu; Chen Jing (Petroleum Research, 2017)
Pressure fields of different sags in a petroliferous basin were significantly different, and it was related to hydrocarbon enrichment. Based on pressure data of different sags in Bohai Bay Basin, types of pressure field and its distribution characteristics were well discussed, and relationships between overpressure and hydrocarbon generation, pressure field and hydrocarbon enrichment were also investigated. Results showed that the Paleogene pressure fields of different sags in Bohai Bay Basin could be divided into three types: normal pressure type, single overpressure type and double overpressure type. These three types of pressure fields had the zoned features in their distributions. The normal pressure fields were mostly distributed in peripheral sags of the basin, while the single overpressure fields were widespread in the basin, and the double overpressure fields were concentrated in the areas around the Bohai Sea. Hydrocarbon generation had a significant effect on overpressure formation, thus overpressure horizons generally were corresponded to major source rock horizons, and differences of filling evolution history and main hydrocarbon-generation strata of different sags might be important factors for the formation of these three types of pressure fields. Overpressure in source rock horizons was closely related to hydrocarbon enrichment. Horizontally, hydrocarbons were mainly distributed around the overpressure center, and the secondary migration distance of hydrocarbons was affected by the degree of overpressure. Vertically, hydrocarbon distribution was controlled by the type of pressure fields. Hydrocarbons in the normal pressure sags were mainly enriched in the major hydrocarbon-generation horizons and their adjacent horizons, hydrocarbons in the single overpressure sags were mainly distributed in the hydrocarbon-generation horizons and its upper and lower horizons, while in the double overpressure sags, the hydrocarbon enrichment degree in Neogene was high. Hydrocarbon enrichment in sags was controlled by the degree of overpressure in hydrocarbon-generation horizons, and these oil-rich sags had relatively large overpressure degree. Keywords: Overpressure, Hydrostatic pressure, Pressure field, Hydrocarbon generation, Hydrocarbon enrichment, Sag, Bohai bay basin